The Genomic Characteristics of ALK Fusion Positive Tumors in Chinese NSCLC Patients - Liu, Shaokun; Huang, Tanxiao; Liu, Ming; He, Wenlong; Zhao, YingShen; Yang, Lizhen; Long, Yingjiao; Zong, Dandan; Zeng, Huihui; Liu, Yuanyuan; Liao, Wenting; Duan, Jingxian; et al. (Frontiers in Oncology, 2020)
Anaplastic lymphoma kinase (ALK) fusion events account for ~3–7% genetic alterations in patients with non-small cell lung cancer (NSCLC). In this study, we identified the ALK fusion patterns and a novel ALK fusion partner in 44 ALK positive NSCLC patients using a customized HapOncoCDx panel, and identified ALK fusion partners. The most common partner is EML4, forming the variant 1 (v1, E13:A20, 18/44), variant 2 (v2, E20:A20, 5/44), and variant 3 (v3, E6:A20, 13/44). Moreover, we detected a new ALK fusion partner HMBOX1. At the mutation level, TP53 is the most frequently mutated gene (24%), followed by ALK (12%) and STED2 (12%). The median tumor mutation burden (TMB) of these samples is 2.29 mutations/Mb, ranging from 0.76 mut/Mb to 16.79 muts/Mb. We further elaborately portrayed the TP53 mutation sites on the peptide sequence of the encoded protein by lollipop. The mutational signature and copy number alterations (CNAs) of the samples were also analyzed. The CNA events were found in 13 (13/44) patients, and the most commonly amplified genes were MDM2 (n = 4/13) and TERT (n = 4/13). Together, these results may guide personalized clinical management of patients with ALK fusion in the era of precision medicine.